(untitled) (Research, Society and Development, 2021)
The chemical composition and bioactivity of green coffee is influenced by both intrinsic and extrinsic factors, and it is a rich source of bioactive compounds, including phenolic compounds, alkaloids, and many compounds with antioxidant and anti-inflammatory properties. These characteristics have sparked numerous studies on its chemical composition and, consequently, have been attributed numerous advantages and disadvantages for human health. This study aimed to quantify the total phenolic constituents and analyze the in vitro antioxidant activity of green coffee from the Conquista Plateau region, Bahia, Brazil, and separate them according to their antioxidant potential. The total phenolic content (TPC) was determined and the evaluation of the in vitro antioxidant potential was investigated by the DPPH radical scavenging methods and the β-carotene:linoleic acid (BCLA) system co-oxidation method. Principal component analysis (PCA) was applied to reveal which samples showed higher and lower antioxidant potential. The results showed that the samples presented moderate content of total phenolic constituents 27.02 mg. g-1 of sample, low primary antioxidant activity with the average value of 65.17 EC50 mg. g-1 sample and moderate secondary antioxidant activity with 44% protection from oxidation of the β-carotene molecules present, moderately inhibiting the conditions favorable to oxidation that were inserted during the analysis. The principal components analysis proved efficient in the separation and classification of the green coffee samples, allowing the observation of the dispersion and heterogeneity among the samples, demonstrating different composition and bioactivity profiles.